Pawn Gold for Financing Arrum Hajj at Palu Barat Branch Powder - Fatmah; Abdul Halik; Muhammad Syafry Firman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Performing the pilgrimage is one of the wishes of all Muslims who seek to achieve it throughout their lives as a form of perfecting worship in the pillars of Islam. However, not all Muslims have the opportunity to carry out worship in the holy land because the implementation of the pilgrimage requires material and physical preparation. And mentally strong to carry out the worship. Besides that, the quota available for prospective Indonesian pilgrims set by the Saudi Arabian government is also limited when compared to the total Muslim population in Indonesia, which must be divided among 34 provinces in Indonesia. Therefore, the waiting list for pilgrims is increasing every year due to the increasing number of applicants for Hajj. Therefore, PT. Pegadaian Syariah makes the Arrum Hajj product, which is a gold pawning program for hajj financing for economically weak people who want to go on pilgrimage, through this product, people can register for hajj and simultaneously obtain a haj portion number.